Pengaruh Pendidikan Sebaya (Peer Education) Terhadap Sikap Dalam Pencegahan Anemia Pada Remaja Putri Di Posyandu Remaja Desa Pandes Klaten - Aulia Putti Utari; Gita Kostania; Suroso Suroso (Poltekkes Kemenkes Surakarta, 2019)
Background: The prevalence of anemia is still high among teenage girls aged 15-24 years (18,4%), it can be caused by several things, one of them is due to the lack of public awareness (especially teenagers) about the prevention of iron deficiency anemia. To overcome this, it is necessary to intervene more upstream to groups of youth and teenegers. One of them is by increasing the knowledge of teenegers through peer education. Peers has a very high influence in attitudes. This is caused by teens tend to choose the same attitude with their peers to be accepted by the group. The purpose of this study is to determine the effect of peer education on attitudes about anemia prevention among teenage girls in “Posyandu” Pandes, Klaten. Method: The type of this study was a Pre-Experiment design with one group pre-post test approach. Sampling technique that used was cluster sampling, the number of samples obtained 60 teenage girls as respondents in Pandes, Klaten. Data collected was using questionnaires on anemia prevention and data analysis technique that used was paired t-test parametric statistic with significance level of 0,05. Results: The attitude of teenage girls in anemia prevention is positive with pretest’s mean was 51,42 and posttest’s mean was 53,92. Conclusion: The p-value indicated the result of 0,001 (p < 0,05). Peer education had an effect on attitude in anemia prevention.